Crescimento e produção de feijão-caupi sob efeito de veranico nos sistemas de plantio direto e convencional - Freitas, Rômulo Magno Oliveira de (Universidade Federal Rural do Semi-Árido, 2012)
The cowpea crop has great importance for the Brazilian Northeast, especially for the poorest population. One of the major problems encountered for this crop is drought stress caused by erratic rainfall, coupled with the high temperatures common in this region. The no-tillage system has features, such as reduction of soil water evaporation, higher water retention and lower soil temperature fluctuations, and can be a way to minimize the water stress in a cowpea crop. Thus, this study aims to obtain information on growth, yield components and cowpea yield under moisture stress in no-tillage and conventional crop systems. For this purpose an experiment was conducted at Universidade Federal Rural do Semi-Arido, in a split plot with randomized complete blocks design with four replications, using the cowpea cultivar BRS Guariba, and no-tillage and conventional crop systems treatments. For the dry spells simulation, irrigation systems has been suspended at 34 days after sowing, during the onset of flowering, for periods of 2, 6, 10, 14, 18 and 22 days, after what the irrigation was resumed. To evaluate the effect of the crop systems and moisture stress on growth, samples were taken between 15 and 64 days after sowing, in the treatments with and without irrigation (22 days duration). The evaluation of yield components (pod length, number of grains per pod, number of pods per plant and hundred grains weight) and yield was performed at 70 days after sowing. The tillage systems influenced the leaf area, and stem leaf, pod and plant dry weight. The growth rates were influenced by the plant phenological phase (age) and by water stress. The highest growth rates were achieved in the no-tillage system. Water stress affected negatively all the variables, regardless of tillage system. The no-tillage system was more productive both for the irrigated and the stress treatments. The dry spells periods affected grain yield and all other yield components studied in a negative way, except for the hundred grains weight. Among the systems studied, the no-tillage system provides higher values for the yield components, except for the hundred grains weight
Growth and yield of cowpea under dry spell in conventional and no tillage crop systems
Keywords: Vignaunguiculata (L.); Water stress; Mulch, Dry matter accumulation, grain yield; Vignaunguiculata (L.) Walp.; Estresse hídrico; Cobertura morta; Acúmulo de matéria seca; Rendimento de grãos; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA